Welfare effects of property taxation - Max Löffler; Sebastian Siegloch (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We investigate the welfare implications of property taxation. We apply a sufficient statistics approach that accounts for the distributional effects of tax changes at the household level within a spatial equilibrium framework. We show that equity effects are driven by price adjustments in the housing and labor markets, while efficiency is determined by changes in public goods. Using microdata and exploiting 5,500 municipal property tax changes in Germany, where assessed housing values remain constant, we find that 83 percent of the tax burden is passed through to rental prices, with modest labor market effects. Simulations of the welfare effects of property taxes reveal that the price effects of property tax hikes are regressive. Despite the low efficiency costs of the tax, it becomes distributionally neutral only if public good preferences are very high.
Keywords: H22; H41; H71; R13; R31; R38; 330; property taxation; welfare; tax incidence; local labor markets; rental housing